Testing a Prediction Method for Multivariate Budgets - Lev, Baruch (Journal of Accounting Research, 1969)
This paper reports an empirical test of the usefulness of a prediction method for multivariate budgets suggested by Theil.' The method, based on information theory concepts, is described in the first three sections, and results of the test are presented in the remaining sections. These results show that the suggested prediction method outperforms both the actual forecasts made by the firms who provided the data and two naive forecasts.